Relação entre carga parasitária de cães naturalmente acometidos por leishmaniose visceral e infectividade para Lutzomyia longipalpis: Lilian Aparecida Colebrusco Rodas. - - Rodas, Lilian Aparecida Colebrusco [UNESP] (2014)
Visceral leishmaniasis is a severe disease that has the dog as its main domestic reservoir. Gaps in the knowledge difficult even more the control of this disease. Regarding the canine reservoir, the possibility of establishing infectivity indicators, like the dogs parasite load, could result in better characterization of its role as source of infection in the transmission chain. Xenodiagnosis in dogs with visceral leishmaniasis were performed with subsequent parasite load evaluation of the host and the vectors, using sandflies captured in the urban area of Araçatuba,SP. After five days, the female sand flies were dissected, subjected to parasitological evaluation by the direct demonstration of the parasite (DDP) and by counting in a Neubauer chamber (NC). A kinetoplast DNA fragment of Leishmania spp. was amplified by conventional PCR and by qPCR to check the presence and quantification of Leishmania kDNA. Dogs were assessed for clinical signs and blood, skin and conjunctival swab samples were taken and tested for parasite load. The diagnostic methods tested (NC, PCR and qPCR) were correlated by linear regression and positivity results were corrected by the natural infection rate. Conventional PCR and qPCR proved to be appropriate for evaluating canine infectivity. There was a correlation between the parasite load present in the dog' skin and the conjunctive swab, as well as with the sandflies parasite loads. Principal component analysis revealed that some of the clinical signs shown by the dogs were related to a highest sandfly infection rate.